Current Landscape: The Mechanism and Therapeutic Impact of Obesity for Breast Cancer - Zhao, Chongru; Hu, Weijie; Xu, Yi; Wang, Dawei; Wang, Yichen; Lv, Wenchang; Xiong, Mingchen; Yi, Yi; Wang, Haiping; Zhang, Qi; Wu, Yiping (Frontiers in Oncology, 2021)
Obesity is defined as a chronic disease induced by an imbalance of energy homeostasis. Obesity is a widespread health problem with increasing prevalence worldwide. Breast cancer (BC) has already been the most common cancer and one of the leading causes of cancer death in women worldwide. Nowadays, the impact of the rising prevalence of obesity has been recognized as a nonnegligible issue for BC development, outcome, and management. Adipokines, insulin and insulin-like growth factor, sex hormone and the chronic inflammation state play critical roles in the vicious crosstalk between obesity and BC. Furthermore, obesity can affect the efficacy and side effects of multiple therapies such as surgery, radiotherapy, chemotherapy, endocrine therapy, immunotherapy and weight management of BC. In this review, we focus on the current landscape of the mechanisms of obesity in fueling BC and the impact of obesity on diverse therapeutic interventions. An in-depth exploration of the underlying mechanisms linking obesity and BC will improve the efficiency of the existing treatments and even provide novel treatment strategies for BC treatment.